Generation and preclinical evaluation of a human heavy-chain-only antibody recognizing the membrane-bound tumor-associated antigen mesothelin - Janssens, Rick; van Haperen, Rien; van der Reijden, Michael; Maas, Alex; Wang, Jingsong; Grosveld, Frank; Drabek, Dubravka (Frontiers in Chemical Biology, 2024)
Objective: Mesothelin (MSLN) is an attractive target for anti-cancer therapeutics and bioimaging reagents that make use of antibodies. This study aimed to develop a novel human anti-MSLN single domain antibody which will exclusively bind to the membrane attached MSLN using transgenic mice that generate human heavy chain only antibodies (HCAb) and explore the resulting HCAb as an imaging tool. Methods: We have introduced a doxycycline inducible human MSLN gene in genetically modified mice expressing human heavy chain only antibodies (HCAbs). This new way of noninvasive immunization by antigen induction results in MSLN antigen production in its native conformation on the cell surface. Screening of 2000 HCAbs from the resulting immune library yielded numerous binders, from which we chose 19G6 as the lead antibody. The antibody was 111 Indium radiolabeled and tested in a xenotransplantation tumor model with OVCAR-3 cells. Results: 19G6 shows nanomolar affinity towards membrane bound mesothelin. It does not recognize soluble MSLN. In an in vivo mouse model, the human MSLN positive tumours were visualized. Non labelled antibody given in excess prevented binding, showing tumour specificity. Conclusions: 19G6 with a human Fc is a promising tumour cell tracer in vivo. The HCAb can also be engineered into a smaller and shorter lived tracer (only the VH domain) or be combined with other targets binding domains to form multispecific modalities for tumour immunotherapy.